2019
DOI: 10.1073/pnas.1810070116
|View full text |Cite
|
Sign up to set email alerts
|

Concentric organization of A- and B-type lamins predicts their distinct roles in the spatial organization and stability of the nuclear lamina

Abstract: The nuclear lamina is an intermediate filament meshwork adjacent to the inner nuclear membrane (INM) that plays a critical role in maintaining nuclear shape and regulating gene expression through chromatin interactions. Studies have demonstrated that A- and B-type lamins, the filamentous proteins that make up the nuclear lamina, form independent but interacting networks. However, whether these lamin subtypes exhibit a distinct spatial organization or whether their organization has any functional consequences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 47 publications
8
123
0
Order By: Relevance
“…In order to test this hypothesis, it is necessary to explore the space-time compaction and accessibility of CDs. Super-resolved fluorescence microscopy, including single molecule localization microscopy (SMLM) and stochastic optical reconstruction microscopy (STORM), may become the methods of choice to measure absolute differences of DNA/chromatin compaction with spatial resolution at the nanometer scale [79, 84, 85], whereas chromatin accessibility can be probed indirectly with methods that allow to measure molecular diffusion rates [8689].…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this hypothesis, it is necessary to explore the space-time compaction and accessibility of CDs. Super-resolved fluorescence microscopy, including single molecule localization microscopy (SMLM) and stochastic optical reconstruction microscopy (STORM), may become the methods of choice to measure absolute differences of DNA/chromatin compaction with spatial resolution at the nanometer scale [79, 84, 85], whereas chromatin accessibility can be probed indirectly with methods that allow to measure molecular diffusion rates [8689].…”
Section: Discussionmentioning
confidence: 99%
“…B‐type lamins result from expression of two distinct genes, namely LMNB1 and LMNB2, originating lamin B1 and B2 isoforms, respectively. Interestingly, while the B‐type lamins form a looser network closely associated with the INM, the A‐type lamins’ network is more tightly spaced and remain in proximity to the INM facing the nucleoplasm (Delbarre et al, 2006; Goldberg, Huttenlauch, Hutchison, & Stick, 2008; Nmezi et al, 2019; Shimi et al, 2008, 2015; Xie et al, 2016). Another interesting aspect is that the lamins bind directly to chromatin via the lamina‐associated domains (LADs).…”
Section: Introductionmentioning
confidence: 99%
“…A prediction based on this difference in the lamina incorporation pathways is that Lamin A and B-type Lamins build the foundation of the nuclear lamina meshwork, on which Lamin C meshwork assembles. While exact localization of Lamin C within the nuclear lamina has not yet been defined, a recent study using super-resolution microscopy reported that localization of Lamin A/C (detected by an antibody recognizing both Lamin A and C) is closer to the nuclear interior than Lamin B1 within the nuclear lamina meshwork [ 67 ]. Thus, one possibility is that Lamin C is most accessible by kinases of all lamin subtypes within the nuclear lamina by virtue of their differential localization within the nuclear lamina.…”
Section: Nuclear Lamin Phosphorylation In Interphasementioning
confidence: 99%